1994
DOI: 10.1084/jem.179.2.609
|View full text |Cite
|
Sign up to set email alerts
|

Clonal populations of T cells in normal elderly humans: the T cell equivalent to "benign monoclonal gammapathy".

Abstract: SummaryTo determine whether T cells, like B cells, can become clonally expanded in normal individuals as a function of age, we compared the T cell VB repertoire of cord blood to that of peripheral blood from normal donors over 65 yr of age. T cells from elderly subjects contained expanded subsets (greater than the mean + three standard deviations) ofT cell receptor (TCR) VB populations. These expanded subsets were observed primarily among CDS, but not CD4 cells, represented up to 37.5% of all CD8 cells, and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
473
1
8

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 737 publications
(512 citation statements)
references
References 37 publications
30
473
1
8
Order By: Relevance
“…In contrast, comparison between the patient groups showed a higher frequency of CD8ϩ,CD28-null T cells in patients with extraarticular RA than in those with limited RA (P Ͻ 0.05). Consistent with previous reports (24), younger healthy persons (ages 19-34 years) had a significantly lower frequency of CD8ϩ,CD28-null T cells than older healthy persons ages Ն39 years (P Յ 0.008). The latter finding also indicates an influence of age on CD28 loss in CD8ϩ T cells.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast, comparison between the patient groups showed a higher frequency of CD8ϩ,CD28-null T cells in patients with extraarticular RA than in those with limited RA (P Ͻ 0.05). Consistent with previous reports (24), younger healthy persons (ages 19-34 years) had a significantly lower frequency of CD8ϩ,CD28-null T cells than older healthy persons ages Ն39 years (P Յ 0.008). The latter finding also indicates an influence of age on CD28 loss in CD8ϩ T cells.…”
Section: Resultssupporting
confidence: 91%
“…In contrast, there is an even higher level of in vivo accumulation of CD56ϩ T cells among RA patients, which is disproportionate with age. Similar age-related in vivo accumulation of CD28-null T cells has been reported (23,24), whereas RA patients have even higher frequencies irrespective of age (8,9) (Figure 2A). These findings support the idea of accelerated senescence in 54 MICHEL ET AL RA (17), with CD28-null,CD56ϩ T cells being prototypic senescent or presenescent lymphocytes.…”
Section: Discussionsupporting
confidence: 83%
“…From the Old template, five clusters appeared to be memory CD4 T cells (CD3+CD4+CD8−CD45−), three expressed monocytic markers (CD3−CD14+CD11B+), and four expressed both T cell and monocyte markers and showed high FSC‐W values, consistent with T cell/monocyte conjugates. The T cell results fit well with previous studies that showed a shift in frequency from naïve to memory CD8 T cells on aging 18, 19, 20, 21, consistent with the accumulation of memory cells with continued antigen stimulation, and oligoclonal expansion of specific memory CD8 T cell populations 22, 23. Similarly, a decrease in gamma‐delta T cells has been reported previously 24, 25.…”
Section: Resultssupporting
confidence: 90%
“…In such circumstances, only single-cell gene rearrangement study of tumor-infiltrating T-lymphocytes in non-Hodgkin's B-cell lymphoma-affected tissues could address this issue (52). Clonal populations of nonneoplastic T-cells have also been described in patients with B-cell chronic lymphocytic leukemia and multiple myeloma (53,54) and even in healthy elderly humans (55).…”
Section: Discussionmentioning
confidence: 99%